A high-field functional MRI study of quadri-lingual subjects - Briellmann, Regula S; Saling, Michael M; Connell, Ailie B; Waites, Anthony B; Abbott, David F; Jackson, Graeme D (Brain and language, 2004)
We assessed six multilingual subjects by functional MRI using a Noun Verb Generation task in four different languages. We hypothesised that the degree of proficiency in each language would be related to the extent of functional activity measured in a region of interest analysis. Proficiency in each language was quantified using two neuropsychological tests. All four languages activated overlapping brain areas, corresponding to the major language regions. The number of activated voxels correlated with proficiency, so that the activated volume increased for languages in which a subject had poorer proficiency. Activation did not appear to be dependent on the age at which the language was learnt.